The landscape of the russian geographers: the evolution of the geographical perspective between the nineteenth and the twentieth centuries - Frolova, Marina (UFPR, 2007)
From the eighteenth to the twentieth century, Russian geographydeveloped under the influence of different scientific trendsand social practices. The history of the concept of landscapereveals in a spectacular way the evolution of the geographicalapproach to the environment. By the beginning of the twentiethcentury, ‘landscape’ was viewed as a universal category,and was widely used by the Russian geographers. This term,however, did not appear in Russian geography until the endof the eighteenth century, with the adoption of two words offoreign origin: Landschaft and paysage. For two centuries,these words were synonyms, but by 1930-1940, the termLandschaft had been restricted to a scientific meaning, at atime when the word paysage was beginning to be used to referto scenery. How did the Russian geographical schools affectthe evolution of the word landscape? What led to the divorcebetween the terms Landschaft and paysage? What is the roleof these two words in contemporary Russian geography? Theauthor attempts to explain the particularities of the developmentof Russian geography between the end of the nineteenth andthe end of the twentieth century through the analysis of theevolution of the concept of landscape.